Cool‐Season Annual Grasses Interseeded into a Bermudagrass with Improved Cold Tolerance for Grazing in the Upper South. Issue 1 (1st December 2014) - Aiken, Glen E.
Abstract : Bermudagrass [ Cynodon dactylon (Pers.) L.] cultivars with improved cold tolerance can be used for grazing in the U.S. upper south, but these bermudagrasses do not provide adequate growth for stocking until late May to early June. Length of the grazing season can be extended by interseeding bermudagrass with cool‐season annual grasses; however, it is uncertain if competiveness of cool‐season grasses will reduce yields and damage stands of bermudagrasses that are late in breaking dormancy. A plot experiment was conducted with 'Wrangler' bermudagrass to compare spring and summer herbage dry matter (DM) yields, percentage harvested yields relative to total spring or summer DM yields, and nutritive value among interseeded rye ( Secale cereale L.), ryegrass ( Lolium multiflorum Lam.), wheat ( Triticum aestivum L.), rye–wheat and rye–ryegrass mixtures, and bermudagrass‐only plots. Rye and mixtures of rye with wheat or ryegrass had high total spring yields in both years whereas wheat yields were low in both years and ryegrass provided high yields in the first year and lower yields in the second. Bermudagrass‐only plots consistently had the highest total summer yields, but any dampening of bermudagrass in interseeded plots occurred only in the first summer harvest. Results indicated that cool‐season annual grasses can be interseeded into bermudagrass to provide grazing in the spring with high‐quality forage.